The epigenetics of keloids. Issue 8 (30th June 2021) - Stevenson, Andrew W.; Deng, Zhenjun; Allahham, Amira; Prêle, Cecilia M.; Wood, Fiona M.; Fear, Mark W.
Abstract: Keloid scarring is a fibroproliferative disorder of the skin with unknown pathophysiology, characterised by fibrotic tissue that extends beyond the boundaries of the original wound. Therapeutic options are few and commonly ineffective, with keloids very commonly recurring even after surgery and adjunct treatments. Epigenetics, defined as alterations to the DNA not involving the base‐pair sequence, is a key regulator of cell functions, and aberrant epigenetic modifications have been found to contribute to many pathologies. Multiple studies have examined many different epigenetic modifications in keloids, including DNA methylation, histone modification, microRNAs and long non‐coding RNAs. These studies have established that epigenetic dysregulation exists in keloid scars, and successful future treatment of keloids may involve reverting these aberrant modifications back to those found in normal skin. Here we summarise the clinical and experimental studies available on the epigenetics of keloids, discuss the major open questions and future perspectives on the treatment of this disease.